1975
DOI: 10.1073/pnas.72.3.1063
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP and cyclic GMP concentrations in serum- and density-restricted fibroblast cultures.

Abstract: Mouse fibroblasts transformed by simian virus 40 (SV3T3 cells) are characterized by cyclic AMP and cyclic GMP levels, respectively, about half and twice those found in growing untransformed 3T3 cells. Densitydependent inhibition of growth is correlated with reduced cyclic GMP concentrations in 3T3 and four different density-restricted revertant lines derived from SV3T3. The levels of cyclic AMP are not increased at confluence. Upon serum restriction, serum-dependent cell lines show a greater increase in intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…probably induced by characteristic changes in the ratio of cAMP to cGMP (Moens et al, 1974(Moens et al, , 1975. Previous work has also suggested that CBS is regulated at least in part by cAMP (Goss, 1986).…”
Section: Cells and Hepg2 Cells Under Different Growth Conditionsmentioning
confidence: 91%
“…probably induced by characteristic changes in the ratio of cAMP to cGMP (Moens et al, 1974(Moens et al, , 1975. Previous work has also suggested that CBS is regulated at least in part by cAMP (Goss, 1986).…”
Section: Cells and Hepg2 Cells Under Different Growth Conditionsmentioning
confidence: 91%
“…However, in serum-stimulated 3T3 cells, cyclic AMP levels are greatly decreased (35)(36)(37)(38). On the other hand, cyclic GMP levels have been reported to be increasing (36,37) and this has led others (27) to suggest that this compound may be the S6-phosphokinase activator. But again there is a great deal of controversy concerning whether cyclic GMP levels are increasing or decreasing during this time (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Pruss and Herschman (20) and Pledger and coworkers (22) have shown that in some cell lines the mitogenic activity of EGF is potentiated by cholera toxin, which activates adenylate cyclase thereby raising intracellular cAMP. In addition, earlier studies showed that serum deprivation increased intracellular cAMP in some cell lines (28)(29)(30). We, therefore, determined the cAMP level in density-arrested and serum-deprived A31 cells and found nearly twice as much as in serum-deprived cells (Fig.…”
mentioning
confidence: 99%